RhoB Loss Prevents Streptozotocin-Induced Diabetes and Ameliorates Diabetic Complications in Mice - Bravo-Nuevo, Arturo (American Society for Investigative Pathology, 2011)
RhoB is an early-response gene whose expression is elevated by multiple cellular stresses; this gene plays an important role in cancer, macrophage motility, and apoptosis. These factors are essential for the onset of type 1 diabetes mellitus and related complications. This study explores the role of RhoB in β-cell depletion and hyperglycemia-associated complications and tests whether the pleiotropic effect of statins on glycemic control is RhoB dependent. We induced β-cell depletion in RhoB(+/+), RhoB(+/−), and RhoB(−/−) mice with streptozotocin (STZ). Diabetic status was assessed by glucose tolerance and pancreatic islet loss. RhoB(−/−) mice showed a significant reduction in the severity of STZ-induced diabetes; only 13% of the STZ-treated RhoB-null animals became hyperglycemic, as opposed to 61% of the wild-type controls. Diabetes-related complications, such as wound healing rate and onset of nephropathy, were also assessed. Hyperglycemic RhoB(−/−) mice had fewer signs of nephropathy and showed faster wound healing than RhoB(+/+) animals. After assessing the diabetic status of mice treated simultaneously with STZ and simvastatin, we conclude that the effect of statins in improving glycemic control is RhoB independent. We propose that RhoB is a modifier of diabetes, important for the induction of β-cell loss. Suppression of RhoB expression may have potential application in the treatment of diabetes and associated complications.